2020
DOI: 10.3389/fmicb.2020.565158
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Amphibian Antimicrobial Peptide, Phylloseptin-PV1, Exhibits Effective Anti-staphylococcal Activity Without Inducing Either Hepatic or Renal Toxicity in Mice

Abstract: In order to part address the problem of drug-resistant pathogens, antimicrobial peptides (AMPs) have been proposed as alternatives to traditional antibiotics. Herein, a novel phylloseptin peptide, named phylloseptin-PV1 (PPV1), is described from the defensive skin secretion of the Neotropical white-lined leaf frog, Phyllomedusa vaillantii. The peptide was synthesized by solid phase peptide synthesis (SPPS) and purified by RP-HPLC, prior to assessment of its biological activities. PPV1 not only demonstrated pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
(63 reference statements)
0
12
0
1
Order By: Relevance
“…A wide spectrum of antimicrobial activities of AMPs inspires researchers to search for new active peptides in biological material [ 252 , 253 ], and also serves as the basis for the design of new synthetic compounds [ 254 , 255 ]. To date, information about AMPs is presented in numerous databases describing the structural, functional, allergenic and toxicological properties of these peptide factors of innate immunity [ 256 , 257 , 258 , 259 , 260 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide spectrum of antimicrobial activities of AMPs inspires researchers to search for new active peptides in biological material [ 252 , 253 ], and also serves as the basis for the design of new synthetic compounds [ 254 , 255 ]. To date, information about AMPs is presented in numerous databases describing the structural, functional, allergenic and toxicological properties of these peptide factors of innate immunity [ 256 , 257 , 258 , 259 , 260 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GL-29 and GL-22 exhibited strong potency against the two tested clinical strains, including the cystic fibrosis (CF) isolated strains, S. aureus (B042 V2E1 A) and MRSA (B038 V1S1 A) [ 31 ]. Moreover, these two peptides possessed extraordinary activities against KPC-producing strains, including E. coli (ATCC BAA-2340) and K. pneumoniae (ATCC BAA-1705), which made them valuable for further studies [ 38 , 39 ]. In addition, it is widely accepted that the antibacterial mechanism of AMPs is the membrane permeabilisation mode of action [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Broad-spectrum activity, diversity of mechanisms, fast action, lower risk of resistance and low propensity to develop toxicity are some of the most notable advantages [ 248 ]. Interestingly, in contrast to the high toxicity of available polypeptide antibiotics, many recent in vivo studies have reported that AMPs are safe for animal models [ 70 , 223 , 249 ]. Notably, by testing the lysis of human renal proximal tubular epithelial cells (HRPTEC) in vitro and applying some sequence modifications, the possibility of reduced renal function can be avoided both in vitro and in vivo [ 70 ].…”
Section: Advantages Limitations and Solutionsmentioning
confidence: 99%